Law from the Perspective of Human Rights Protection in Indonesia - Septiana Rachman, Evy (YHMM PUBLISHING, 2024)
As an instrument for regulating activities in cyberspace, the most fundamental threat to freedom of expression-currently-on the internet in Indonesia comes from Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE). This article analyzes how the 2016 ITE Law still and continues to cause problems that violate the principles of freedom of expression and human rights. The research results show that this law still has the potential to suppress and limit the right to freedom of expression and silence criticism. This law causes the public to remain silent about the existing socio-political conditions for fear of being seen as insulting or defaming their good name and thus being sentenced to prison. Therefore, the need to improve several articles becomes very important. In Indonesia, it is also urgent to establish an independent regulatory body that has the authority to explain and limit the regulation of content on the Internet based on human rights principles.